2005
DOI: 10.1093/geront/45.4.486
|View full text |Cite
|
Sign up to set email alerts
|

The Employment of Nurse Practitioners and Physician Assistants in U.S. Nursing Homes

Abstract: More generous state Medicaid nursing home reimbursement and higher competition may advance the investment in medical infrastructure, which in turn may positively affect the quality of care provided to nursing home residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
4
41
0
Order By: Relevance
“…Higher payment rates would facilitate the provision of more medically oriented care as acuity increased but would also provide an incentive to nursing homes to continue to serve their patients in the nursing home. This too is consistent with the finding that nursing facilities in states with higher nursing home Medicaid payment rates are significantly more likely to hire advanced practice nurses and to have higher levels of skilled nurses on staff (Intrator et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Higher payment rates would facilitate the provision of more medically oriented care as acuity increased but would also provide an incentive to nursing homes to continue to serve their patients in the nursing home. This too is consistent with the finding that nursing facilities in states with higher nursing home Medicaid payment rates are significantly more likely to hire advanced practice nurses and to have higher levels of skilled nurses on staff (Intrator et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…18,19 Studies have demonstrated the effectiveness of NPs in providing cost-effective, quality care in nursing homes. 16 Given their education and training in patient assessment, coordination of care, and communication skills, NPs are well suited to direct and deliver care to patients who are living with, and dying of, progressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…From 1993 to 2003, the rate of APN use doubled, with more than 20% of the nation's 16,000 nursing homes using APNs or physician assistants (PAs) in some capacity (Intrator et al, 2005). Two national surveys estimated that between 1,159 (Rosenfeld, Kobayashi, Barber, & Mezey, 2004) and 1,360 (Spratley, Johnson, Sochalski, Fritz, & Spencer, 2001) APNs practiced in nursing homes.…”
mentioning
confidence: 99%